Application of Metaphorical Architecture to the Karo Cultural Center - Istaqli Iman Barus; Sri Gunana Sembiring; Mohammad Dolok Lubis; Novrial (Formosa Journal of Applied Sciences, 2023)
The cultural center functions as a forum for cultural activists, artists, the local community, and local youth to be able to show, sell and preserve local cultural activities. The Karo tribe needs a Cultural Center so that they can preserve culture and appreciate cultural actors in the Karo land, the current generation, especially the Karo youth, are spoiled with entertainment in the form of games such as malls and other entertainment venues. The growing influence of western culture through technology is feared to erode karo cultural values. make people become consumptive and spend time looking at gadgets that are not necessarily useful. The cultural center can be a place to increase knowledge of local culture in order to remain sustainable, restore mindsets and views on good cultural values that can be taken. With the Metaphorical Architecture approach which will later be able to show karo culture and attract visitors to the karo cultural center. The application of this theme is applied to building formations, appearances and forms of buildings.